When (if ever) is discrimination based on reaction qualifications permissible? What do people think? - Andersen, Didde Boisen; Midtgaard, Søren Flinch; Pedersen, Viki Møller Lyngby (Politica, 2023)
To what extent is it permissible for an employer (or a selector on their behalf) to take into consideration how customers might react to certain features of a candidate for a job? This is the question regarding so-called reaction qualifications. A luck egalitarian response to this question emphasizes two moral factors, to wit (i) whether the qualification in question is one that the candidate can affect by choosing appropriately, and (ii) whether the choice in question is associated with values that the candidate holds dear. We test folk intuitions regarding the relevance of these factors for assessing the (il)legitimacy of reaction qualifications and find that the former factor influences people’s assessments, whereas the latter does not.